A new approach to biotransformation and value of kitchen waste oil driven by gut microorganisms in Hermetia illucens - Wang, Yuting; Yu, Zuojian; Cao, Qingcheng; Liu, Cuncheng; Qin, Yuanhang; Wang, Tielin; Wang, Cunwen (Journal of environmental management, 2024)
Hermetia illucens larvae are known for their ability to recycle organic waste, but their capacity to recover waste oils and the role of gut microorganisms in this process are not fully understood. To gain further insights, the biological recovery of waste frying oil into valuable lipids and the influence of gut bacteria on this biotransformation were investigated. The larvae efficiently digested and absorbed waste frying oil, demonstrating their potential for converting various oils into insect fat. The presence of different fatty acids in their diet significantly altered gut bacterial communities, enriching certain genera such as Actinomyces, Enterococcus, and Providencia. Redundancy analysis revealed that the composition and structure of these bacterial communities were predictive of their function in the biotransformation of fatty acids and the lipid biosynthesis in the larvae. Specific bacteria, including Corynebacterium_1, Providencia, Actinomyces, Escherichia-Shigella, and others, were identified to play specialized roles in the digestion and absorption of fatty acids, contributing to lipid synthesis and storage. These findings highlight the potential of Hermetia illucens in the biological recovery of waste frying oil and underscore the crucial role of gut microbiota in this process, offering a sustainable approach to waste management and bioenergy production. [Display omitted] •Hermetia illucens larvae effectively utilize waste oil as a nutritional source.•Gut microbiota play a pivotal role in the digestion of fatty acids from waste oil.•Gut bacteria mediate lipid biosynthesis in the larvae.•Hermetia illucens offer a sustainable approach in waste-to-energy conversion.